2021
DOI: 10.1002/lt.26061
|View full text |Cite
|
Sign up to set email alerts
|

Propensity Score–Matched Analysis of Posttransplant Outcomes in Living Donor Liver Transplantation for Older Adult Recipients

Abstract: The impact of increasing recipient age on morbidity and mortality following living donor liver transplantation (LDLT) remains controversial. The study aims to analyze the impact of recipient age on outcomes following LDLT. Data on adult LDLTs performed between November 2009 and February 2020 were retrieved from a prospectively maintained database. Patients were stratified into 2 groups based on recipient age: 18 to 65 years (younger adults) and >65 years (older adults). Propensity score matching (PSM) using ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 44 publications
(55 reference statements)
0
9
0
Order By: Relevance
“…However, as specific comparison between older and younger recipients was not performed 28 . Most of the other reported experience is from single center reports, evaluating outcomes of adults ≥60–65y compared to younger LDLT recipients 29–36 . The present study is the first, to the best of our knowledge, specifically comparing outcomes of adult recipients ≥70y old undergoing LDLT versus DDLT.…”
Section: Discussionmentioning
confidence: 95%
“…However, as specific comparison between older and younger recipients was not performed 28 . Most of the other reported experience is from single center reports, evaluating outcomes of adults ≥60–65y compared to younger LDLT recipients 29–36 . The present study is the first, to the best of our knowledge, specifically comparing outcomes of adult recipients ≥70y old undergoing LDLT versus DDLT.…”
Section: Discussionmentioning
confidence: 95%
“…26 However, recent data suggest that older patients can successfully undergo LDLT, and increased utilization may reduce waitlist death by allowing older patients to undergo transplant with lower severity of illness and decreased risk of sarcopenia. 27 Etiology and severity of ESLD have been clearly associated with reduced utilization of LDLT in the United States. Patients with high MELD scores appear to have less physiologic reserve, less ability to survive early allograft dysfunction from a partial graft, and a higher rate of perioperative complications.…”
Section: Discussionmentioning
confidence: 99%
“…In the A2ALL analysis, lack of acceptable donors was raised as a possible issue, given restrictions on the age of eligible donors 26 . However, recent data suggest that older patients can successfully undergo LDLT, and increased utilization may reduce waitlist death by allowing older patients to undergo transplant with lower severity of illness and decreased risk of sarcopenia 27 …”
Section: Discussionmentioning
confidence: 99%
“…(3)(4)(5)(6)(7) In this issue of Liver Transplantation, Hakeem et al assessed the impact of older recipients (aged >65 years) on the outcomes of LDLT by analyzing prospectively collected data from a large cohort of LDLTs performed at a single institute in India during a span of over 10 years. (8) The authors compared the outcomes of this population to their younger cohort of LDLT recipients (aged 18-65 years) by means of propensity score matching for preoperative recipient and donor parameters associated with LDLT outcomes. They demonstrated that recipient age is correlated with worse outcomes after LDLT, as the elderly group had higher rates of early 30-day and 90-day mortality, which leads to reduced long-term (1-year and 5-year) survival compared with younger LDLT recipients.…”
Section: See Article On Page 1273mentioning
confidence: 99%